213k views
0 votes
Y - 3 = -2 ( x + 5 ) in standard form

User Mementum
by
5.2k points

1 Answer

4 votes

Answer:

2x + y = -7

Explanation:

Standard form is Ax + By = C

A represents the coefficient with x

B represents the coefficient with y

C represents the constants

1 - Rewrite to make it easier to work it out

y - 3 = -2 ( x + 5 )

2 - Distribute

y - 3 = -2x - 10

3 - Get the variables on one side and the constants on the other

y - 3 = -2x - 10

+ 2x + 2x

2x + y - 3 = -10

+ 3 + 3

2x + y = -7

Hope this helps,

User Robbie Liu
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.